THE STRUCTURE OF THE ALKALOID OF YOLOXOCHITL - SODI PALLARES, ERNESTO; MARTINEZ GARZA, HECTOR (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1903)
After studying the structure and evolution of the silicotic node with the Ag impregnation methods of Rio-Hortega, the following conclusions were reached The histologic basis of all lesions induced in the human lung by siliceous dust is the proliferation
ARCH BIOCHEM
Keywords: STRUCTURE, ALKALOID, YOLOXOCHITL; CIENCIAS DE LA VIDA; BIOLOGIA MOLECULAR; BIOLOGIA MOLECULAR DE MICROORGANISMOS